Վանի շրջանային վարչության անվտագության և պաշտպանական գործառույթները որպես պետականության դրսևորման ձև - Հարությունյան, Ավետիս (ԱրՊՀ հրատ․)
The district department of Van is creating a bunch of undertakings, which will guarantee a possibility of living a safe and independent life. In the May of 1917, to provide public order and security, lawful execution of orders, and, as well as, to support the V Regiment, a regional police force was set up leaded by police authorities Levon Shaghoyan and Grigor the Bulgarian (Grigor Bulgharaci.) Great measures were taken in Van to give weapons and military training to young people. In case of an attack, the soldiers would retreat in the direction of supporting the army and playing the role of the city's safe-keepers and guardians. List writings were held for that purpose, and three instructors were separated. Районное управление Вана осушествило ряд мероприятий, направленных на гарантирование безопасной и независимой жизни. Для обеспечения общественного порядка и безопасности, исполнение государственных законов, а также в целях поддержки армянского V полка, в мае 1917 года была создана областная полиция во главе с Левоном Шагояном и Григором Болгарским (Григор Булгараци). В короткие сроки полиция Вана показала свое значимость.
Keywords: Հասարակական կարգ; Վան